Genome-wide identification and functional characterization of oleosin genes in peanut (Arachis hypogaea L.) - Hu, Meiling; Wu, Jie; Xue, Xiaomeng; Huang, Li; Liu, Nian; Yan, Liying; Chen, Yuning; Wang, Xin; Kang, Yanping; Wang, Zhihui; Jiang, Huifang; Liao, Boshou; et al. (Frontiers in Plant Science, 2025)
Peanut is a worldwide important oil crop and serves as a major source of vegetable oil. Seed oil is stored as oil bodies (OB), which are subcellular structures in the cytoplasm. Oil bodies accumulate triacylglycerols (TAGs) inside and surrounded by a monolayer of phospholipids (PL) with oil-body-membrane proteins. Oleosins have been demonstrate to be the predominant oil-body-membrane proteins and played a crucial role in maintaining oil body stability. In this study, 12 oleosin genes were identified in peanut, distributed across 9 chromosomes and classified into three lineages (U, SH, and SL). Most AhOle genes exhibited high expression levels in developing seeds, a pattern that aligns with the expression profiles of U, SH, and SL oleosins. Several cis-elements were found in the promoters of AhOle genes, such as LTR, ABRE, and TCA-element. Expression analysis confirmed that these genes were responsive to treatments involving drought, cold stress and various plant hormones. The AhOle11 gene was cloned due to its highest expression level observed during seed development. Subcellular localization analysis demonstrated that AhOle11 gene was localized in oil bodies. Overexpression AhOle11 in Arabidopsis significantly increased in seed oil content and an increased oil body density, thereby supporting its critical role in oil accumulation. Nevertheless, the fatty acid profiles in transgenic seeds exhibited only minor alterations. This study contributes to a comprehensive understanding of the oleosin family in peanut and provides valuable insights for genetic improvement aimed at enhancing oil accumulation.